Determinants of growth of the flammable grass, Triodia scariosa: Consequences for fuel dynamics under climate change in the Mediterranean region of South Eastern Australia. (25th February 2016) - Gibson, Rebecca K.; Bradstock, Ross A.; Penman, Trent; Keith, David A.; Driscoll, Don A.
Abstract: Environmental conditions may influence the presence and strength of competitive interactions between different life forms, thereby shaping community composition and structure, and corresponding fuel dynamics. Woodland and shrubland communities of the Mediterranean climate region of South Eastern Australia contain a varied mixture of herbaceous and woody plants. The ratio of herbaceous to woody plants changes along gradients of temperature, moisture and soil fertility. This study aimed to experimentally examine the relative importance of, and interactions between environmental controls (moisture and soil fertility) on the balance of dominant herbaceous ( Triodia scariosa ) and woody plants (e.g. Acacia ligulata and Leptospermum coriaceum ) and their ultimate effects on fuel and fire regimes. The results suggest that environmental determinants of the growth of T . scariosa are likely to be more important than interactions with shrubs in controlling the distribution of T . scariosa . The growth of T . scariosa was consistently higher under hot temperatures and on the less fertile yellow sands, which dominate the south of the region. The results suggest that there is strong potential for the distribution and abundance of T . scariosa to be altered in the future with changes in temperature associated with climate change. The distribution of soil types across the Mediterranean climate region of South Eastern Australia may be predisposed to favour the southerly expansion of T . scariosa ‐dominated communities in the future under a warmer climate.